Cerebrovascular Disease in the Setting of Posterior Reversible Encephalopathy Syndrome - XiaoQing Cheng (Frontiers Media S.A., 2021)
Overlap between the pathogenesis of posterior reversible encephalopathy syndrome and that of cerebrovascular disease can confound their clinical and radiological presentations, posing a diagnostic challenge. This article presents a literature review and discussion of the clinical manifestations, pathological mechanisms, and imaging manifestations of subarachnoid hemorrhage and vasculitis leading to posterior reversible encephalopathy syndrome, coexistence of posterior reversible encephalopathy syndrome with reversible cerebral vasoconstriction syndrome, and hemorrhage and infarction secondary to posterior reversible encephalopathy syndrome. The findings show that posterior reversible encephalopathy syndrome shares some overlapping pathophysiological mechanisms with cerebrovascular disease. Importantly, neuroimaging plays an important role in identifying this entity in a timely manner and differentiating it from other diseases.